The Influence Of Work Culture And Work Ethic On The Perfomance Of Assembling Departement Employees At PT Adis Dimension Footwear Tangerang Regency - Kusumo, Johani; Fahmi, Khaerul; Setiawan, Temmy (Faculty of Science and Technology University of Pramita Indonesia, 2026)
This study aims to determine: (1) the partial effect of work culture on employee performance; (2) the partial effect of work ethic on employee performance; (3) the simultaneous effect of work culture and work ethic on employee performance.This study uses a quantitative descriptive method, which describes variables as they are, supported by numerical data generated from actual conditions. The population in this study was all employees in the Assembly division at PT. Adis Dimension Footwear Balaraja- Tangerang. The research sample consisted of 84 respondents. This study used a saturated sampling technique due to the small population size; therefore, the sample in this study used the entire population of 84 employees as respondents. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used multiple linear regression analysis with SPSS 26. Data validity was obtained through a partial t-test and a simultaneous F-test.The results of this study indicate that (1) partially, work culture has a t-test effect on the performance of employees in the Assembly division at PT. Adis Dimension Footwear Balaraja- Tangerang, which is indicated by the calculated t value> t table (5.774>1.990) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, job training significantly influences the performance of employees in the Assembling section at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (9.937>1.990) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected.(3) Simultaneously, work culture and job training significantly influence the performance of employees in the Assembling section at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by F count> F table (147.881>3.11) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected.Based on the research results, it can be concluded that work culture and work ethic, both partially and simultaneously, have a significant influence on employee performance in the assembly department at PT. Adis Dimension Footwear Balaraja-Tangerang.